Yucatan 1512 - Vede, Alex; Vede, Alex (Dark Horse Books, a division of Dark Horse Comics LLC, 2025)
During the conquest of the Yucatan Peninsula in 1512, Spanish soldier Sorolla saves a Mayan child and escapes into the jungle where they encounter monstrous warriors guarding the ancient city.